2022
DOI: 10.1039/d1qo01879e
|View full text |Cite
|
Sign up to set email alerts
|

Penaloidines A and B: two unprecedented pyridine alkaloids from Penicillium sp. KYJ-6

Abstract: Penaloidines A (1) and B (2), a pair of epimers, unprecedented meroterpenoid pyridine alkaloids possessing a tetrahydrofuro[3,2-c][2,7]naphthyridinyl scaffold, were characterized from Penicillium sp. KYJ-6. Their structures were elucidated by spectroscopic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Water molecules were deleted and the polar hydrogen atoms, charge, and magnetic field were added before docking. AutoDock Tools 1.5.6 ( https://autodock.scripps.edu ) was used for molecular docking and processing of ligands and receptors ( Zheng et al, 2021 ; Gan et al, 2022 ). Active pockets were built and saved as protein data bank (PDB), partial charge (Q), and atom type (T) (PDBQT) files.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water molecules were deleted and the polar hydrogen atoms, charge, and magnetic field were added before docking. AutoDock Tools 1.5.6 ( https://autodock.scripps.edu ) was used for molecular docking and processing of ligands and receptors ( Zheng et al, 2021 ; Gan et al, 2022 ). Active pockets were built and saved as protein data bank (PDB), partial charge (Q), and atom type (T) (PDBQT) files.…”
Section: Methodsmentioning
confidence: 99%
“…It can overcome water retention, promote circulation of Qi ( Chen and Xu, 2003 ), remove blood stasis, staunch bleeding, expel sores and carbuncles, dispel pathogenic wind, remove edema, and stop itching ( Editorial Committee of Flora Reipublicae Popularis Sinicae, 1997 ). It can be used as a hemostatic agent for bleeding due to external injury, and as a treatment for tumors, ulcers, edema, abdominal mass, abdominal distension, ascites due to liver cirrhosis, and skin itching ( Wu et al, 1992 ; Chen et al, 2014 ; Gan et al, 2022 ). E. nematocypha is also used to treat bruises, stiffness, indigestion, toothache, and diabetes mellitus ( Roy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the methyl group on the cycloesadienone of penicitrinone H is essential for inhibitory activity when compared with its B analogue [ 141 ], while palitantin was reported to be significantly more potent than its analogue 13-hydroxypalitantin [ 142 ]. Some quantitative differences have also been found among stereoisomers, such as (+)- and (-)-penicilliumine [ 143 ], quinolactacins A1–A2 [ 144 ], and penaloidines A–B, which are unprecedented pyridine alkaloids possessing a tetrahydrofuro[3,2-c][2,7]naphthyridinyl scaffold [ 145 ].…”
Section: Effects On the Nervous Systemmentioning
confidence: 99%
“…Reassignment of the structures of pestalopyrones A-D was reported by Wang et al 101 Polychlorinated cyclopentenes from a marine derived Periconia sp. were studied by Oberlies et al 102 Ding et al 103 reported on penaloidines A and B: two unprecedented pyridine alkaloids from Penicillium sp. Hamann et al 104 reported on structure and antimicrobial activity of rare lactone lipids from the sooty mold.…”
Section: Nuclear Shielding Calculation In Natural Productsmentioning
confidence: 99%